A Case Study on Rare Occurance of Geriatric Intussusception with Lipoma as The Leading Point - Risdiarta, Rosalia Septaviana; Guanawan, Jimmy Indarto; Nugroho, Daniel C.A.; Prastoatmodjo, Radityo (The Indonesian Society for Digestive Endoscopy, 2025)
Intussusception is commonly found in the early years of infancy but is considered rare in adult patients. There are no specific symptoms for intussusception in adults, as it is typically seen in infants; hence, radiology imaging is a major key to determining the diagnosis. We presented a case where a 77-year-old male patient presented with persistent abdominal pain, distension, and bloody stool 4 days before an emergency department (ED) visit. The patient was referred from another healthcare facility after receiving a normal result of USG. A 3-view abdominal x-ray was performed, which revealed ileus with large bowel obstruction. The abdominal CT-scan later revealed a sausage-like sign, suggestive of a colo-colic intussusception with a large mass of fat as the leading point and pneumo-peritoneum. Abdominal CT-Scan showed the detailed imaging of how and where the intussusception is occurring and what seems to be the root problem. The laparotomy surgery report also confirmed the colo-colic intussusception with lipoma as the primary cause. Hence, radiology plays a crucial role in diagnosing the tumor leading to intussusception in the preoperative setting. Among the imaging techniques, abdominal CT scan has emerged as the preferred method due to its high sensitivity and ability to provide detailed information, which is essential for therapeutic management. This case report aimed to highlight the importance of radiological imaging, particularly abdominal CT scan, in diagnosing adult intussusception with a neoplastic leading point, and to present a rare case of colo-colic intussusception caused by a lipoma in an elderly patient.